ISLAMIC LAW AND LOCAL WISDOM: EXPLORING LEGAL SCIENTIFIC POTENTIAL IN INTEGRATING LOCAL CULTURAL VALUES - Insani, Nur; B., Sumiyati; Karimullah, Suud Sarim; Gnan, Yavuz; Sulastri, Sulastri (Kanun Jurnal Ilmu Hukum, 2024)
This study provides a richer and more holistic view of how Islamic law and local cultural values can be integrated effectively and harmoniously in regulating the lives of heterogeneous Muslim communities. The research method adopted in this study is library research with an integrative and comprehensive literature analysis approach to identify concepts, theories, techniques, and findings that have been put forward by previous researchers regarding the relationship between Islamic law and local wisdom by looking for patterns, similarities, differences, and trends that emerge from the analyzed literature. The results show that Islamic law, through its flexible conceptual framework, facilitates the integration of local cultural values into legal practice, maintaining its relevance in diverse social and cultural contexts. This integration process not only strengthens local cultural identity in the face of globalization but also supports social harmony by defusing cultural conflicts and strengthening community coherence. Furthermore, it creates an inclusive and fair legal system, recognizing and respecting individual diversity. This integration contributes to knowledge development by demonstrating how laws adaptive to cultural contexts can support sustainability and social justice in heterogeneous societies.